STRUCTURAL ADJUSTMENT OF RATS’ GUMS MUCOSA AFTER THE METHACRYLATE INTRODUCTION - Gerasimenko, S.B. (World of Medicine and Biology, 2016)
Effect of 1% methyl ester of methacrylic acid solution for 14 days leads to structural changes in the mucosa of rats’gum attached parts which appear of epithelial thickening of the plate due to the increase in the rows of cells in the corneum and spinosum layesr. The number of intraepithelial lymphocytes increased. In the lamina propria developing vascular congestion of hemomicrocirculatory bed and perivascular edema. Up to 30 days of observation set the seal horny scales and flattening of granular layer’s cells, the number of mast cells increased in the lamina propria. These histological findings were confirmed at the morphometric study. Installed histological and morphometric changes of gum’s attached part mucosa of rats caused a direct irritant effect of 1% methyl ester of methacrylic acid, and changes in the microcirculation system, that causing a disruption of the mucosa’s components trophics.